Spelling Errors in Student Articles in the Online Journal of the Faculty of Social and Political Sciences, University of Riau, Edition I January-June 2022 - Nasya Putri Veradini; Charlina Charlina; Tria Putri Mustika (CV. Rayyan Dwi Bharata, 2024)
This research aims to describe spelling errors found in student articles in the online journal of the Faculty of Social and Political Sciences, Riau University, Edition I January-June 2022. The method used is a qualitative method with reading techniques and note-taking techniques. The data analysis method used is to reduce the data, then proceed with presenting the data and drawing conclusions from the data analysis that has been carried out. Based on data research, the data obtained was 600 data from spelling errors which were divided into 156 data on errors in the use of letters, 102 data on errors in the use of punctuation marks, and 342 data on errors in writing words.